2023
DOI: 10.1002/advs.202206869
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectionally Regulating Viral and Cellular Ferroptosis with Metastable Iron Sulfide Against Influenza Virus

Abstract: Influenza virus with numerous subtypes and frequent variation limits the development of high-efficacy and broad-spectrum antiviral strategy. Here, a novel multi-antiviral metastable iron sulfides (mFeS) against various influenza A/B subtype viruses is developed. This work finds that mFeS induces high levels of lipid peroxidation and •OH free radicals in the conservative viral envelope, which depends on Fe 2+ . This phenomenon, termed as a viral ferroptosis, results in the loss of viral infectibility and pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 70 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…Unlike conventional antiviral approaches, the polysulfides released by the broad‐spectrum antiviral metastable iron sulfides (mFeS) inhibit intracellular viral replication through inhibition of lipid peroxidation and ferroptosis in cells, thus enabling effective treatment of influenza viruses. [ 19 ] Other studies have also demonstrated that exogenously supplied and endogenously produced polysulfides significantly scavenge intracellular free radicals, which is derived from the autocatalytic cycle of polysulfides and the interconversion between GSH and GSSH. [ 27 , 66 ] Notably, polysulfides hold the ability to rapidly penetrate cell membranes and thus exert their antioxidant effects intracellularly in a time manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike conventional antiviral approaches, the polysulfides released by the broad‐spectrum antiviral metastable iron sulfides (mFeS) inhibit intracellular viral replication through inhibition of lipid peroxidation and ferroptosis in cells, thus enabling effective treatment of influenza viruses. [ 19 ] Other studies have also demonstrated that exogenously supplied and endogenously produced polysulfides significantly scavenge intracellular free radicals, which is derived from the autocatalytic cycle of polysulfides and the interconversion between GSH and GSSH. [ 27 , 66 ] Notably, polysulfides hold the ability to rapidly penetrate cell membranes and thus exert their antioxidant effects intracellularly in a time manner.…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 , 16 , 17 , 18 ] Previous studies have shown that conventional iron sulfide only exerts antioxidant effects by the release of polysulfides. [ 19 , 20 , 21 ] However, the release of polysulfides from iron sulfide is less efficient. Moreover, the composition of iron sulfide is not homogeneous and is always accompanied by the production of impurities.…”
Section: Introductionmentioning
confidence: 99%